Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1556/2006.2021.00042
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional and online-specific Fear of Missing Out are associated with the development of IUD symptoms in different internet applications

Abstract: Background and aims An increasing number of people experience negative consequences from the excessive use of different Internet applications or sites (e.g., Instagram, League of Legends, YouTube). These consequences have been referred to as specific Internet Use Disorders (IUDs). The present study aims to examine the Fear of Missing Out (FoMO) on rewarding experiences with respect to specific Internet activities. FoMO has been found to mediate the link between psychopathology and symptoms of In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…The SEM results showed that state-FoMO did not predict loneliness, but trait-FoMO positively predicted loneliness, suggesting that trait-FoMO rather than state-FoMO increased the risk of loneliness. The results support the view of Wegmann et al (2017) that FoMO is indeed a complex construct and that trait-FoMO is more problematic than state-FoMO (Röttinger et al, 2021). The results of the present study also showed that interpersonal relationship satisfaction was associated with low trait-FoMO but not significantly associated with state-FoMO.…”
Section: Positive and Negative Mechanisms Of Active Social Media Use ...supporting
confidence: 89%
See 1 more Smart Citation
“…The SEM results showed that state-FoMO did not predict loneliness, but trait-FoMO positively predicted loneliness, suggesting that trait-FoMO rather than state-FoMO increased the risk of loneliness. The results support the view of Wegmann et al (2017) that FoMO is indeed a complex construct and that trait-FoMO is more problematic than state-FoMO (Röttinger et al, 2021). The results of the present study also showed that interpersonal relationship satisfaction was associated with low trait-FoMO but not significantly associated with state-FoMO.…”
Section: Positive and Negative Mechanisms Of Active Social Media Use ...supporting
confidence: 89%
“…State-FoMO refers to the concerns about missing information online. It is an unstable cognitive bias apparent during certain online activities, including social media use (Wegmann et al, 2017 ; Röttinger et al, 2021 ). That is, state-FoMO is directly caused by frequent internet usage (Wegmann et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with a growing number of studies we observed a positive association between higher levels of FOMO and more problematic smartphone and social media usage. On the one hand, FOMO has for instance been associated with development of problematic usage of a number of internet applications, including problematic internet usage (Röttinger et al, 2021) and smartphone addiction (Alinejad, Parizad, Yarmohammadi, & Radfar, 2022). However, on the other hand, an increasing number of studies underscore the role of social and self-related cognitions in this association such that the association between FOMO and smartphone addiction is mediated by loneliness (Alinejad et al, 2022) while FOMO mediates the association between parental support, self-construal, self-concept clarity or interpersonal sensitivity with problematic smartphone use (Kim, 2022; Lin et al, 2021; Servidio, Sinatra, Griffiths, & Monacis, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence from different lines of research suggests an association between dispositional FOMO and problematic Internet use - in particular in the domains of social media and smartphone use - as well as associated emotional dysregulations and detrimental effects on daily life (Röttinger et al, 2021; Akbari et al, 2021; Rozgonjuk, Sindermann, Elhai, & Montag, 2020; Elhai, Yang, Rozgonjuk, & Montag, 2020; Yuan, Elhai, & Hall, 2021). Current conceptualizations propose that FOMO represents a general trait-like predisposition rendering individuals at an increased risk for excessive and problematic social media engagement and ultimately the development and maintenance of Internet Use Disorders (Akbari et al, 2021; Elhai et al, 2021; Röttinger et al, 2021). For associations between FOMO and age, gender and the Big Five of Personality see (Rozgonjuk, Sindermann, Elhai, & Montag, 2021)…”
Section: Introductionmentioning
confidence: 99%
“…FoMO also played an important role in increased sensitivity to stress which is associated with neglect and problematic SNS use, and these in turn were associated with negative emotions ( 67 ). Finally, FoMO mediated the association between mental health and symptoms of Internet Use Disorder (IUD) ( 68 ).…”
Section: Emotional and Social Factors Associated With Problematic Sns...mentioning
confidence: 99%